Current implications of past DDT indoor spraying in Oman - Booij, Petra; Holoubek, Ivan; Klánová, Jana; Kohoutek, Jiří; Dvorská, Alice; Magulová, Katarína; Al-Zadjali, Said; Čupr, Pavel (The Science of the total environment, 2016)
In Oman, DDT was sprayed indoors during an intensive malaria eradication program between 1976 and 1992. DDT can remain for years after spraying and is associated with potential health risk. This raises the concern for human exposure in areas where DDT was used for indoor spraying. Twelve houses in three regions with a different history of DDT indoor spraying were chosen for a sampling campaign in 2005 to determine p,p'-dichlorodiphenyltrichloroethane (p,p'-DDT), p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE) and p,p'-dichlorodiphenyldichloroethane (p,p'-DDD) levels in indoor air, dust, and outdoor soil. Although DDT was only sprayed indoor, p,p'-DDT, p,p'-DDE and p,p'-DDD were also found in outdoor soil. The results indicate that release and exposure continue for years after cessation of spraying. The predicted cancer risk based on concentrations determined in 2005, indicate that there was still a significant cancer risk up to 13 to 16years after indoor DDT spraying. A novel approach, based on region-specific half-lives, was used to predict concentrations in 2015 and showed that more than 21years after spraying, cancer risk for exposure to indoor air, dust, and outdoor soil are acceptable in Oman for adults and young children. The model can be used for other locations and countries to predict prospective exposure of contaminants based on indoor experimental measurements and knowledge about the spraying time-schedule to extrapolate region-specific half-lives and predict effects on the human population years after spraying.
Keywords: Oman; znečištění vzduchu ve vnitřním prostředí; vystavení vlivu životního prostředí; moskyti - kontrola; Insecticides; Environmental Exposure; Adult; Human risk assessment; dítě; Air Pollution, Indoor; Child; Mosquito Control; Residual indoor spraying; Humans; DDT; Omán; Region-specific half-life; insekticidy; Cancer risk; dospělí; lidé